A study of Shanxi Traditional Music Guzheng Teaching Guidebook in Shanxi Vocational University of Engineering Science and Technology in Shanxi Province - Haixia, He; Yodwised, Chutasiri; Suwanmanee, Suvicha (Journal of Roi Kaensarn Academi, 2024)
This study adopts the method of mixed research, the combination of qualitative and quantitative research method, select Taiyuan Preschool teachers college 8 music education professional students as the experiment object, children's songs and piano accompaniment teaching experiment, the researchers use qualitative research method, interview the experts, observed the Taiyuan preschool teachers college music education professional second grade students learning status. In the development stage, the quantitative analysis method describes the experimental design and conclusions statistical analysis. The paper analyzed the effect of students using children's song piano accompaniment practice book through three formative tests and summative tests. Research results were for the weak point that students can't perform piano accompaniment for children's songs, formulated the Taiyuan Preschool teachers college music education students piano accompaniment of children's songs exercise book teaching plan, including "children's songs theoretical knowledge","Basic exercise of piano accompaniment", "For children's songs configured with simple harmony music type of piano accompaniment exercise ", "Creation four hands play children's songs piano accompaniment " four parts. This exercise book teaching plan is completed after expert interview, aiming to discuss how to teach piano accompaniment for children's songs, which can mobilize students' interest in learning piano accompaniment, help students improve their piano accompaniment ability, and successfully obtain the purpose of students' preschool teacher qualification certificate.